Comparison of the safety and efficacy of radiofrequency thermocoagulation with percutaneous balloon compression for treating trigeminal neuralgia: a systematic review and meta-analysis - Wu, Zeyu; Zhao, Yongming; Liu, Jiang; Fan, Yiyue; Yang, Ying (Frontiers in Neurology, 2023)
Objective This study aimed to systematically assess the efficacy and complications of radiofrequency thermocoagulation (RFT) and percutaneous balloon compression (PBC) for treating trigeminal neuralgia (TN). Methods Chinese and English studies on RFT and PBC in the treatment of TN were systematically searched using CNKI, Wanfang Data, VIP, PubMed, EMBASE, Cochrane Library, and until December 31, 2022. Further, the literature was strictly screened using specific inclusion and exclusion criteria. The RevMan 5.4 software was used for data processing and meta-analysis. Results Overall, 16 studies with 3,326 patients were included. The results of meta-analysis revealed that no significant difference was present between the two groups in terms of the rate of efficacy immediately after surgery, 1 month after surgery, and 3 months after surgery (odds ratio [OR] = 0.73, 95% confidence interval [CI] 0.35–1.54, p = 0.41; OR = 0.41, 95% CI 0.13–1.32, p = 0.13; OR = 0.40, 95% CI 0.10–1.60, p = 0.20); however, at 12 months after surgery, the difference was statistically significant (OR = 0.27, 95% CI 0.10–0.75, p = 0.01). Notably, there was no significant difference in the postoperative sleep quality index between the two groups immediately after surgery and 1 month after surgery (SMD = −0.01, 95% CI −2.47 to 2.44, p = 0.99; SMD = 0.14, 95% CI −3.95 to 4.22, p = 0.95). Further, statistically significant differences were observed between the two groups in the incidence of postoperative masticatory muscle strength decline and oral herpes (OR = 0.37; 95% CI 0.21–0.63, p = 0.0003; OR = 0.25, 95% CI 0.10–0.61, p = 0.003). In addition, a statistically significant difference was found in the recurrence rate at 1-year follow-up (OR = 2.23, 95% CI 1.03–4.81, p = 0.04); however, no statistically significant differences were found in the recurrence rate at the 2-year follow-up (OR = 1.95, 95% CI 0.33–11.59, p = 0.46). Conclusion In the treatment of TN, both RFT and PBC can achieve good short-term efficacy, and no significant differences were noted between the outcomes of the two approaches. Compared with RFT, PBC may result in a lower pain score and recurrence rate in the medium and long terms, but it is a higher incidence of cold sores, and the decrease of masticatory muscle strength is more obvious.